ANATOMY OF CRISIS IN THE POLITICAL POWER MECHANISM IN UKRAINE: STRUCTURAL REFORMS VERSUS POLITICAL CONJUNCTURE - Анатольевич, Шатило Владимир (Teisė, 2016)
Problems of constitutional crisis in the political power mechanism in Ukraine are discussed. Relations between structural, institutional and legal factors necessitating institutional reforms in the political power of present-day Ukraine are outlined. Relations between President of Ukraine, legal power and executive power are analyzed. Recommendations are made on amendments in the Constitution of Ukraine. The conclusions are made regarding the legal and political background for reforms of the political power mechanism in present-day Ukraine.